THU0100 PHYSICAL FUNCTION IN RA PATIENTS IN REMISSION UNDERGOING TAPERING AND/OR STOPPING OF DMARDS. (June 2019) - Stephan, Marlene; Tascilar, Koray; Hagen, Melanie; Haschka, Judith; Reiser, Michaela; Hartmann, Fabian; Kleyer, Arnd; Hueber, Axel; Manger, Bernhard; Figuereido, Camille; Cobra, Jayme; Tony, Hans-Peter; et al.
Abstract : Background: Several studies including our own RETRO study have shown that tapering or stopping disease modifying anti-rheumatic drugs (DMARDs) in rheumatoid arthritis (RA) patients in sustained remission is feasible (1-3). However, tapering/stopping bears the risk of decline in physical function as some patients may relapse and face increased disease activity. Objectives: Here we analysed the impact of tapering or stopping DMARD treatment on the physical function of RA patients, who were randomized into continuation, tapering or stopping DMARD treatment in the RETRO study. Methods: RETRO is a multicentre, parallel-group phase 3 trial in which RA patients in stable DAS-28-ESR remission were randomized to (i) DMARD tapering, (ii) stopping DMARDs after a 24-week-taper or (iii) control strategy that continued DMARDS. 1, 2, 3 HAQ and DAS-28 scores were measured at 0, 3, 6, 9 and 12 months. 1, 2 Functional worsening was defined as a HAQ increase of≥0.25. We calculated incidences of functional worsening (per 100 person-months) in each treatment group with 95% Poisson confidence intervals and plotted event-free survival by treatment arm. The effect of treatment reduction strategy on functional worsening was assessed in a recurrent-event Cox regression model with control, taper or taper/stop group as the predictor. Results: 201 patients were analysed. In 44 patients functional worsening was observed. Incidence (95%CI) of functional worsening was in the control 1.48 (0.77-2.59), taper 1.74 (0.95-2.92) and taper/stop arm 1.96 (1.16-3.10). The incidences suggest higher probability of functional worsening in tapering and/or stopping DMARDs, however at the end of study, functional worsening was similar among the groups (Figure). Thus, in comparison to the control group, hazard ratio (HR) (95%CI) for functional worsening was 1.21 (0.56 -2.62) in the taper arm and 1.32 (0.76-2.60) in the taper/stop arm. Conclusion: Point estimates and survival curves show that functional decline after tapering or stopping DMARDs in RA patients with stable remission is small. Although the incidence figures suggest a trend these results do not reject with good certainty the null hypothesis of no worsening in functional status. Reference: [1] Haschka, J. et al. 2016; 2 Rech, J. et al. 2016; 3 Hagen, M. et al. 2018 Disclosure of Interests: Marlene Stephan: None declared, Koray Tascilar: None declared, Melanie Hagen: None declared, Judith Haschka: None declared, Michaela Reiser: None declared, Fabian Hartmann: None declared, Arnd Kleyer Grant/research support from: Lilly, Consultant for: Lilly, Speakers bureau: Abbvie, Axel Hueber Grant/research support from: Novartis, Pfizer, Consultant for: Lilly, Speakers bureau: Lilly, Novartis, Janssen, Abbvie, Bernhard Manger: None declared, Camille Figuereido: None declared, Jayme Cobra: None declared, Hans-Peter Tony Consultant for: Eli Lilly and Company, Speakers bureau: Eli Lilly and Company, Stephanie Finzel: None declared, Stefan Kleinert Grant/research support from: Novartis, Consultant for: Novartis, UCB, Chugai, Celgene, Medac, Roche, Abbvie, Speakers bureau: Novartis, UCB, Chugai, Celgene, Medac, Roche, Abbvie, Joerg Wendler: None declared, Florian Schuch Consultant for: Celgene, Lilly, UCB, Roche, Sanofi-Aventis, Abbvie, Novartis, Speakers bureau: Celgene, Lilly, UCB, Roche, Sanofi-Aventis, Abbvie, Monika Ronneberger: None declared, Martin Feuchtenberger: None declared, Martin Fleck: None declared, Karin Manger: None declared, Wolfgang Ochs: None declared, Matthias Schmitt-Haendle: None declared, Hanns-Martin Lorenz: None declared, Hubert Nuesslein: None declared, Rieke Alten Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, Jörg Henes: None declared, Klaus Krueger: None declared, Georg Schett: None declared, Jürgen Rech Grant/research support from: Bristol-Myers Squibb and Celgene (greater than 10, 000), Consultant for: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than 10, 000), Speakers bureau: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than 10, 000)